Twentieth general report on the activities of the European communities 1986 (Office for Official Publications of the EuropeanCommunities Luxembourg-VilleLU, 1987)
Reports on Community activities over the past year. Describes the Community's institutions, its information activities, and the financing of all its programmes. Discusses efforts at building the Community focussing on economic and monetary policy, industrial strategy, research and technology, employment, education and social policy, environment, inter alia. Summarizes main developments in external relations and discusses relations with a number of countries including those of the ACP regions.
IDS